Lake-specific controls on the long-term stability of mining-related, legacy arsenic contamination and geochemical baselines in a changing northern environment, Tundra Mine, Northwest Territories, Canada - Clare Miller; Parsons, MB; Jamieson, HE (2019)
Climate change is influencing the biogeochemistry of northern lake ecosystems. These changes may affect the mobility of naturally occurring metal(loid)s and long-term stability of anthropogenic contaminants. Arsenic (As) concentrations in lake sediments in the Courageous Lake Greenstone Belt, Northwest Territories, Canada, are elevated from the operation of two high-grade, low-tonnage historical gold mines (Tundra Mine and Salmita Mine) and the weathering of mineralized bedrock. In sensitive sub-Arctic environments, it is not currently known how the cumulative effects of resource extraction and climate warming will impact geochemical baselines and the long-term stability of legacy contaminants. In this study, measurements of As concentration and speciation in waters and sediments are combined with multivariate analyses of climate proxies (sediment particle size and organic matter composition) from five lakes downstream of the former Tundra Mine site. Data from lake sediment cores were divided into geochemically distinct populations using a combination of radiometric dating and constrained incremental sum-of-squares cluster analysis to define geochemical baselines, examine the lake-specific controls on As distribution, and determine climate-related factors that may influence the long-term stability of As. Median As concentrations in near-surface impacted sediments (median: 110 mg kg −1 range: 31–1,010 mg kg −1 n = 22) and pre-mining sediment (median: 40 mg kg −1 range: 28–170 mg kg −1 n = 102) exceed the Canadian Council of the Ministers of the Environment Probable Effects Level of 17 mg kg −1 . Near the Tundra Mine, the long-term stability of As in the near-surface sediment is influenced by the source of As (direct disposal and weathering of waste rock, tailings overtopping and seepage, discharge of treated tailings effluent, weathering and airborne deposition of tailings and waste rock, and natural weathering of mineralized bedrock), lithology of the sediment, and composition of sediment organic matter. ...